1996
DOI: 10.1093/humrep/11.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of sperm quality in young healthy Belgian men

Abstract: We have retrospectively analysed the sperm characteristics of 416 consecutive healthy young men who presented themselves in the past 19 years as candidate sperm donors. Ejaculate volume increased slightly (P = 0.067), and average sperm concentration decreased (P = 0.035) by 12.4 x 10(6)/ml over the observation period, so that sperm count per ejaculate remained unchanged (P = 0.91). In contrast, sperm morphology (r = - 0.23, P < 0.0001), rapid progressive motility (r = - 0.42, P < 0.0001) and total motility (r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
0
8

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(114 citation statements)
references
References 16 publications
7
99
0
8
Order By: Relevance
“…[1][2][3][4][5][6][7][8] By contrast, other studies have shown no evidence of deteriorating semen quality. [9][10][11][12][13][14][15][16] Some studies concern infertile couples, while others analyse normal sperm parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] By contrast, other studies have shown no evidence of deteriorating semen quality. [9][10][11][12][13][14][15][16] Some studies concern infertile couples, while others analyse normal sperm parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these changes have been accompanied by a significant decline in semen quality (8)(9)(10). The causes of the increasing incidence of abnormalities in male reproductive function are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Testicular cancer and other male reproductive problems are increasing and may be attributed to endocrine disruptors in the environment as well (Davis et al, 2007;Toppari et al, 1996;Adami et al, 1994). Other studies show that over the past 50 years there has been a steady decline in human sperm count which could be attributed to estrogenic effects (Carlsen 1992;Auger 1995;VanWaeleghem 1996). Additional studies have shown that endocrine disrupting chemicals are linked to developmental deficiencies and learning disabilities in children (EPA, 2001).…”
Section: Discussionmentioning
confidence: 99%